Indian Ginseng - Bennet, S. S. R.; Sharma, B. K. (Indian Forester, 1983)
Ginseng is a famous Chinese drug used as Panacea and aphrodisiac by Chinese from time immemorial. The principa1 source of Chinese, American and Japanese Ginseng are the tuberons roots of Panax ginseng, P. quinquefolius and P. japonicus respectively. Atleast three species, P. pseudoginseng, P. sikkimensis and P. bipinnaatifida, which are distributed in Eastern Himalaya, are the sources of Indian Ginseng. As the well known medicinal product Sanchi of China, used for treating various ailments including cancer, is prepared from P. pseudnginseng the cultivation of the species should be undertaken in East Himalayan region between 1,000 and 2,000 m of altitude. Indian Ginseng species are endongered and should be protected.